Laparoscopic repair of left paraduodenal hernia in an adult: case report and literature review - Sedik, Alaa; Elsayed, Mostafa; Maali, Mufid; Haraga, Abdehamid; Touhahria, Meriam; Elhoushy, Salwa (International Surgery Journal, 2019)
An internal hernia is a protrusion of bowel through a normal or abnormal orifice in the peritoneum or mesentery and the resulting hernia remains intraperitoneal. The para-duodenal type is the most common type of congenital internal hernias. We reported a case of left paraduodenal hernia, who presented with recurrent attacks of severe abdominal pain and occasional vomiting. The case was diagnosed as a left huge paraduodenal hernia, and prepared for a laparoscopic repair after which he made uneventful recovery and remained free of symptoms when he was seen for follow up in surgery outpatient clinic.